Pathways to psychiatric care in Debre Berhan, Ethiopia: A cross-sectional study - Kaleab Berhanu; Abayneh Birlie; Tizibt Fiseha; Yared Reta; Yohannes Gebreegziabhere (PLoS ONE, 2025)
Background Pathways to care are the steps individuals went through before finally consulting formal psychiatric services. In developing countries, people with mental disorders (PWMDs) often first consult traditional or religious healers, which may delay treatment. Although studies from different part of Ethiopia confirm this trend, factors influencing indirect pathways remain insufficiently explored. Objective This study aimed to identify pathways to psychiatric care and factors associated with indirect pathways among PWMDs who received psychiatric care from Debre Berhan Comprehensive Specialized Hospital, Ethiopia. Methods We enrolled 446 PWMDs and used the World Health Organization pathway to psychiatric care encounter form to elicit the pathways to psychiatric care. We conducted a multivariable binary logistic regression analysis to identify factors significantly associated with indirect pathways. Result Most of the PWMDs in the study (72.9%) went through indirect pathways. From sociodemographic characteristics, being in the age group between 41–50 years (AOR = 8.27; 95% CI (2.94, 23.18)) and over 50 years (AOR = 6.46; 95% CI (2.00, 20.82)), being female (AOR = 2.51; 95% CI (1.34, 4.73)), being primary school attendees (AOR = 3.00; 95% CI (1.20, 7.40)), being farmer (AOR = 13.00; 95% CI (3.11, 54.31)), and living in the same house with 4–8 people (AOR = 2.77; 95% CI (1.11, 6.95)) were found to be significantly associated with indirect pathways. While from clinical characteristics, a diagnosis of bipolar disorder (AOR = 2.66; 95% CI (1.10, 6.50)) and anxiety (AOR = 3.94; 95% CI (1.37, 11.34)), perceived stigma (AOR = 5.86; 95% CI (3.00, 11.45)), and facing problems during the help-seeking process (AOR = 0.44; 95% CI (0.21, 0.90)) were found to be significantly associated with indirect pathways. Conclusion In this population, PWMDs primarily used indirect pathways as their first point of contact. Several demographic and clinical factors were significantly associated with utilizing indirect pathways. This study has implications for reducing delays by enhancing psychiatric service integration and establishing effective referral systems.